Splenic immunotoxicity in developing cane toads (Rhinella marina) from Bermuda. (30th June 2016) - Fort, Douglas J.; Mathis, Michael; Fort, Chelsea E.; Fort, Hayley M.; Fort, Troy D.; Linzey, Donald W.; Bacon, Jamie P.
Abstract: The impacts of contaminated sediment from 2 ponds in Bermuda on immune function in newly metamorphosed cane toads were examined. In the present study, a partial life‐cycle experiment exposing Gosner stage 20 cane toad tadpoles to pond sediment and laboratory culture water through metamorphosis and into a juvenile state was performed. A basic immunology battery, including general necropsy, spleen somatic index, spleen white pulp content, splenocyte tissue density, and splenocyte viability, was conducted in newly metamorphosed Rhinella marina exposed to Bermuda freshwater sediment and baseline specimens collected from 2 separate populations in south Texas and south Florida, USA. Immune function was evaluated using a lymphocyte proliferation assay with subset specimens infected with Mycobacterium chelonae . In the Bermuda population exposed to pond sediment, splenocyte tissue density was markedly lower and lymphocyte proliferation substantially less relative to cohorts exposed to control sediment and to the North American populations. Considerable increases in spleen weight and liver and spleen lesions related to M. chelonae infection were recorded in challenged Bermuda R. marina compared with unchallenged specimens. Overall, immune function in Bermuda R. marina was compromised compared with North American mainland R. marina regardless of treatment but more dramatically in specimens exposed to Bermuda pond sediments. Environ Toxicol Chem 2016;35:2604–2612. © 2016 SETAC